2014
DOI: 10.1186/1471-2164-15-88
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-34c is associated with emphysema severity and modulates SERPINE1 expression

Abstract: BackgroundMicroRNAs (MiRNA) are small non-coding RNAs that regulate gene expression. The aim of this study was to identify miRNAs differentially expressed between mild and moderately emphysematous lung, as well as their functional target mRNAs. Resected lung from patients with COPD undergoing lung cancer surgery was profiled using miRNA (Agilent Human miRNA profiler G4470 V1.01) and mRNA (OperonV2.0) microarrays. Cells of lung origin (BEAS-2B and HFL1) were profiled using mRNA microarrays (Illumina HumanHT-12 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
66
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(72 citation statements)
references
References 41 publications
(49 reference statements)
3
66
0
2
Order By: Relevance
“…Dres and colleagues (6) measured Ptr,stim as a surrogate for transdiaphragmatic twitch pressure (Pdi,stim). Laghi and colleagues (12) measured Pdi,stim directly (although Ptr,stim and Pdi,stim are correlated [13,14]). Of greater importance than what was measured, is how it was measured and how it was verified.…”
Section: Editorialsmentioning
confidence: 99%
See 2 more Smart Citations
“…Dres and colleagues (6) measured Ptr,stim as a surrogate for transdiaphragmatic twitch pressure (Pdi,stim). Laghi and colleagues (12) measured Pdi,stim directly (although Ptr,stim and Pdi,stim are correlated [13,14]). Of greater importance than what was measured, is how it was measured and how it was verified.…”
Section: Editorialsmentioning
confidence: 99%
“…To obtain accurate twitch pressures, stimulating probes must be in close proximity to the phrenic nerves (12). Rigorous strategy is imperative to achieve this goal: one nerve is stimulated at a time while monitoring electromyography and pressure (13,14). Once the probe has been positioned where it elicits the strongest signal, investigators repeat the process on the other phrenic nerve.…”
Section: Editorialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a COPD study that focused on the screening of serum miRNAs found that miR-34c-5p is significantly dys-regulated in COPD patients as compared to the healthy controls [17]. In addition, miR-34c modulates the expression of its putative target gene, SERPINE1, in vitro in respiratory cell lines and ex vivo in emphysematous lung tissue [18].…”
Section: Data Exploration With Multiple Co-inertia Analysis (Mcia)mentioning
confidence: 99%
“…Снижение уровня miR-34c в плацентар-ной ткани ведет к повышению экспрессии гена PAI1 [17]. Это может вызывать снижение инвазии трофобласта на ранних сроках бере-менности и повышение свертываемости крови, обусловливая ухудшение маточно-плацентар-ного кровотока, отложения фибрина в маточ-ных сосудах и микроциркуляторном русле пла-центы, то есть способствовать развитию ПЭ.…”
unclassified